2016
DOI: 10.1307/mmj/1480734020
|View full text |Cite
|
Sign up to set email alerts
|

On coxeter mapping classes and fibered alternating links

Abstract: Alternating-sign Hopf plumbing along a tree yields fibered alternating links whose homological monodromy is, up to a sign, conjugate to some alternating-sign Coxeter transformation. Exploiting this tie, we obtain results about the location of zeros of the Alexander polynomial of the fibered link complement implying a strong case of Hoste's conjecture, the trapezoidal conjecture, bi-orderability of the link group, and a sharp lower bound for the homological dilatation of the monodromy of the fibration. The resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Indeed, the union of the constructed multicurves fills the surface (which has boundary, along which we glue in discs to land in the setting we are considering) and components intersect at most once, hence their intersection is minimal. Secondly, the given matrix describing the homological action of φ equals the corresponding matrix product M φ of Penner's construction described in Section 1.1, see [4]. We deduce that for such a mapping class φ realising the Coxeter transformation associated to (Γ, ±), the dilatation equals the spectral radius of the Coxeter transformation associated to (Γ, ±).…”
Section: Coxeter Mapping Classesmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, the union of the constructed multicurves fills the surface (which has boundary, along which we glue in discs to land in the setting we are considering) and components intersect at most once, hence their intersection is minimal. Secondly, the given matrix describing the homological action of φ equals the corresponding matrix product M φ of Penner's construction described in Section 1.1, see [4]. We deduce that for such a mapping class φ realising the Coxeter transformation associated to (Γ, ±), the dilatation equals the spectral radius of the Coxeter transformation associated to (Γ, ±).…”
Section: Coxeter Mapping Classesmentioning
confidence: 83%
“…On the other hand, Hironaka and the author showed that the eigenvalues λ i of the Coxeter transformation corresponding to the Coxeter tree (Γ, ±) with alternating signs are related to the eigenvalues α i of A(Γ) by the equation [4]. Combined, we get that the µ i and the λ i are related by…”
Section: Coxeter Mapping Classesmentioning
confidence: 93%
See 1 more Smart Citation
“…Such a pair (Γ, s) is called a mixed-sign Coxeter graph; cf. [3]. To such a pair, we will associate certain products of reflections.…”
Section: Coxeter Mapping Classesmentioning
confidence: 99%
“…In the case of classical Coxeter trees (Γ, +), A'Campo realised the Coxeter transformation, up to a sign, as the homological action of a mapping class given by the product of two positive Dehn twists along multicurves that intersect each other with the pattern of Γ; see [2]. Similarly, in the case of alternating-sign Coxeter trees (Γ, ±), Hironaka and the author realised the Coxeter transformation, up to a sign, as the homological action of a mapping class given by the product of two Dehn twists of opposite signs along multicurves that intersect each other with the pattern of Γ; see [4]. We call these mapping classes Coxeter mapping classes.…”
Section: Coxeter Mapping Classesmentioning
confidence: 99%